C-1 Substituted isoquinolines potentiate the antimycobacterial activity of rifampicin and ethambutol - Martin, Liam T.; Lamming, Eleanor D.; Maitra, Arundhati; Mortazavi, Parisa N.; Roddan, Rebecca; Ward, John M.; Bhakta, Sanjib; Hailes, Helen C. (Frontiers in Antibiotics, 2023)
The emergence of extensively drug-resistant strains of Mycobacterium tuberculosis threatens decades of progress in the treatment of a disease which remains one of the leading infectious causes of death, worldwide. The development of novel antimycobacterial compounds is therefore essential to reinforce the existing antitubercular drug discovery pipeline. Alongside this approach, there is also interest in new compounds which can synergize with existing antitubercular drugs and can be deployed as part of a combination therapy to increase their activity. This strategy could serve to delay the emergence of resistance to first-line antituberculosis drugs, and increase their efficacy against resistant strains of TB. Previous research has established that several C-1 substituted tetrahydroisoquinolines have antimycobacterial activity. Here, we sought expanded our understanding of their antimycobacterial structure activity relationships and their potential to act as adjunct therapies alongside existing antitubercular drugs. Three chemical series were synthesised and assayed for their antimycobacterial potency, mammalian cell cytotoxicity, inhibition of whole-cell efflux and synergism with isoniazid, rifampicin, and ethambutol. Potent whole-cell efflux inhibitors and synergistic compounds were identified, suggesting potential for development as adjuncts to existing anti-tuberculosis chemotherapy.